Foraminiferal test dissolution reveals severe sediment acidification in estuarine mudflats: new perspectives for present and historical assessment - Fouet, Marie; Daviray, Maxime; Geslin, Emmanuelle; Metzger, Edouard; Jorissen, Frans (Comptes Rendus. Géoscience)
Foraminiferal mudflat communities in the Auray estuary, located along the French Northwest Atlantic coast, were investigated in September 2020. Numerous living specimens of calcareous species showed marks of dissolution. The number of affected individuals, together with their dissolution degree, varied from one site to another. Moreover, pH profiles showed porewater acidification of the subsurface sediment at several stations. We propose two metrics quantifying the degree of dissolution: (i) the “Foraminiferal Test Dissolution” (FTD), based on binocular observations of the foraminiferal community, and (ii) the “Calcareous Test Preservation Ratio” (CTPR), surface ratio (0–0.5 cm) of total living foraminiferal densities (0–1 cm). In stations showing sediment acidification, the O2-pH profiles show the typical biogeochemical signatures of cable bacteria activity (pH increase in the oxic zone followed by strong acidification in the suboxic zone). This suggests that bacterial activity could be responsible for the strong pH decrease leading to corrosive porewaters affecting calcareous tests, hence severe FTD in the first centimetre of sediment leading to high CTPR. Furthermore, observations of FTD in other estuaries on the French Atlantic coast indicate that the phenomenon has become widespread. Re-investigated foraminiferal tests sampled in 1995–1996 in the Auray estuary show no dissolution marks, suggesting that the dissolution process observed in 2020 appeared over the last thirty years. Therefore, the FTD and CTPR could be used as rapid tools to establish the occurrence of dissolution processes, pending geochemical confirmation. The FTD could also be used as sediment acidification proxy in historical records, where geochemical analyses are not possible.